1980
DOI: 10.1093/jn/110.12.2433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fasting on Uterine Blood Flow and Substrate Uptake in Sheep

Abstract: Twelve chronically instrumented late-gestation ewes fasted for 5 days were found to have a 25% decrease in total uterine blood flow and a 20% decrease in placental blood flow. Cardiac output was unchanged but was redistributed, as measured by radiolabeled microspheres, in a pattern similar to that produced by catecholamines. Fasting also was associated with hypoglycemia and altered whole blood amino acid concentrations. Uterine uptakes of glucose, oxygen, essential amino acids and glutamine, an important uteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 25 publications
1
21
2
1
Order By: Relevance
“…In contrast, a 9% decrease in blood pressure was observed by the fifth day of fasting, a change that was similar to what we observed in group 2a animals by the third day. One major difference between the present study and that of Morriss et al 26 was the difference in the provision of calcium in the drinking water. We used deionized water that contained no calcium.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In contrast, a 9% decrease in blood pressure was observed by the fifth day of fasting, a change that was similar to what we observed in group 2a animals by the third day. One major difference between the present study and that of Morriss et al 26 was the difference in the provision of calcium in the drinking water. We used deionized water that contained no calcium.…”
Section: Discussioncontrasting
confidence: 77%
“…Previously, Morriss et al 26 have reported the effect of 5 days of fasting in late gestation ewes. In those studies, in which regular tap water was provided to the animals, none of the four pregnant animals recorded developed hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Complete fasting in ewes carrying singeltons results in lower concentrations of glucose and amino acids in the maternal blood, a marked reduction in uterine blood flow, and decreases in uterine uptake of glucose and amino acids (Morriss et al, 1980). Undernutrition to 70% of nutrient requirements (National Research Council (NRC), 1985) throughout gestation also reduced maternal and foetal concentrations of blood glucose in singeltons' pregnancies (Edwards and McMillen, 2002).…”
Section: Litter-size-dependent Iugr and Nutritional Insultmentioning
confidence: 99%
“…It is also becoming increasingly apparent that changes in maternal body composition and diet not only affect fetal growth and development as a result of direct effects on substrate availability to the fetus, but also indirectly through changes in placental growth and function. Maternal undernutrition in experimental animals and human pregnancy has been associated with reduced placental size and reduced blood flow in uterine and umbilical circulation (11,12). Therefore, a component of the asymmetric fetal growth restriction in undernourished pregnancy in humans and animals is due to a reduction in oxygen as well as nutrient delivery to the fetus.…”
mentioning
confidence: 99%